2017
DOI: 10.1111/jar.12417
|View full text |Cite
|
Sign up to set email alerts
|

Early death and causes of death of people with intellectual disabilities: A systematic review

Abstract: Improved health care, including anticipatory care such as health checks, and initiatives addressing most relevant lifestyle behaviours and health risks are indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
180
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(215 citation statements)
references
References 49 publications
8
180
0
7
Order By: Relevance
“…Synthesis of these studies also revealed that individuals with Down syndrome were less likely to die from causes that could be prevented through public health interventions such as certain cancers and accidents. These findings echoed findings from those of another systematic review that revealed that individuals with intellectual disabilities in general were more likely to die from amenable than preventable causes (O'Leary, Cooper, & Hughes‐McCormack, ).…”
Section: Discussionsupporting
confidence: 69%
“…Synthesis of these studies also revealed that individuals with Down syndrome were less likely to die from causes that could be prevented through public health interventions such as certain cancers and accidents. These findings echoed findings from those of another systematic review that revealed that individuals with intellectual disabilities in general were more likely to die from amenable than preventable causes (O'Leary, Cooper, & Hughes‐McCormack, ).…”
Section: Discussionsupporting
confidence: 69%
“…Individuals with intellectual disabilities (IDs) have more health problems, a poorer general health status, and a shorter life expectancy than individuals in the general population . Coronary heart and respiratory diseases have been identified as the leading causes of death in individuals with IDs .…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory disease and circulatory diseases are the main causes of death of people with ID (O'Leary et al . ). The life expectancy of people with ID has increased over the past few decades, with a shift from sudden deaths and brief illnesses to more lengthy illness processes.…”
Section: Introductionmentioning
confidence: 97%
“…People with intellectual disabilities (ID) have 2.5 times as many health problems as people without ID (van Schrojenstein Lantman-De Valk et al 2000). Respiratory disease and circulatory diseases are the main causes of death of people with ID (O'Leary et al 2018). The life expectancy of people with ID has increased over the past few decades, with a shift from sudden deaths and brief illnesses to more lengthy illness processes.…”
Section: Introductionmentioning
confidence: 99%